STRUKTUR MODAL USAHA KECIL SENTRA KULIT DI SUKAREGANG, GARUT - Budiana Gomulia; Vera Intanie Dewi (Bina Ekonomi, 2011)
Sukaregang Leather craftsmen Centre in Garut is known nationally, and is also a pride of Garutan people, but unfortunately its growth has not shown any outstanding outcomes.  The problem of capital-is mentioned as one of the issues. Meanwhile,  as we know that  the Ministry  of Economic, Small and Medium Enterprises (KEMENKOP) aims at building healthy and strong small, micro and medium enterprises because of its capability to collect its own capital or equity capital and to increase the benefits of credit utilizing as a couple of the reasons. Population of this research is small-scale craftsmen in Sukaregang Leather Craftsmen Centre in Garut taken by purposive sampling. Data collection methodology is focus group discussions and surveys. Purpose of this research is to explain capital structure in general. From the research  on micro- and small-scale entrepreneurs  in Sukaregang  Leather Craftsmen Centre in Garut, we know that: capital structure is not optimum yet, 1). Equity capital accumulation  is very limited; 2). Proportion  of a loan utilized for business  operational,  continuity  and expansion is too little; and 3) There are potencies of ineffective loan utilizing. Researchers  find some worrying facts: a). Both suppliers  and customers are 'still reluctant' to give capital aid; b). Koperasi, BPR, and public banks are known to be able to giant a loan for craftsmen, but high interest rate and other costs, required collateral are factors which inhibit them to get a credit; c). Due  to some middle-scale entrepreneurs who do not pay their credit appropriately,  these entrepreneurs in this center are "black  list”-ed by more than two banks in Garut, making even fewer chances for them (micro-small  entrepreneurs)  to get a loan in standard rate and  free  from demands for various credit requirements,  especially collateral. Researchers suggest  that  to help them to expand, a proper scheme  of capital aid  is needed, which then can be complemented with a scheme of credit-loan from various  financial  institutions  that have been adjusted with the conditions  of these small enterprises.